Analisis Kegunaan Website Kementerian Agama Provinsi DIY dan Provinsi Riau - M. Rafi; Achmad Nurmandi; Syed Agung Afandi (Jurnal Komunikasi, 2020)
At present, the usefulness of the website is seen only as a complement to the services of government agencies, many Ministry of Religion websites have an attractive appearance, but the quality of the information content presented on the website is not always updated. This study aims to analyze the use of the website of the Ministry of Religion of the Special Province of Yogyakarta and Riau Province. The research method used in this study is a qualitative research method to explore a case with data analysis techniques using the help of Nvivo12 Plus software. The results showed that in general the two websites both already have website content that refers to regulations, but in terms of the quality of presenting data, the website of the Ministry of Religion of Riau Province is considered better and meets 3 (three) website usability criteria, namely: Accessibility related to availability and ease of users to access content from a website can be seen from the comparison in terms of ease in understanding the appearance of the number of visitors between the two websites of the Ministry of Religion. second, Easy of use is related to the effort or effort made to use a website or how easily a website can be seen and differences in the availability of data that is still empty in some website columns, and third, namely Customization and Personalization relating to a website that provides content or content dynamic looks of the level of popularity of news on the website. Saat ini, kegunaan dari websiteterlihat hanya sebagai pelengkap dari pelayanan lembaga pemerintahan saja, banyak websiteKementerian Agama yang memiliki tampilan yang menarik, namun kualitas isi informasi yang disajikan di website tidak selalu di perbaharui. Penelitian ini bertujuan untuk menganalisis kegunaan websiteKementerian Agama Provinsi Daerah Istimewa Yogyakarta dan Provinsi Riau. Metode Penelitian yang digunakan dalam penelitian ini adalah metode penelitian kualitatif untuk mengeksplorasi suatu kasus dengan teknik analisis data menggunakan bantuan softwareNvivo12Plus. Hasil penelitian menunjukkan bahwa Secara umum kedua websitesama-sama telah memiliki konten websiteyang mengacu pada regulasi, namun dalam hal kualitas menyajikan data, website Kementerian Agama Provinsi Riau dinilai lebih baik dan memenuhi 3 (tiga) kriteria kegunaan websiteyaitu: Accessibility yang berkaitan dengan ketersediaan dan kemudahan pengguna untuk mengakses konten dari suatu website terlihat dari perbandingan dari sisi kemudahan dalam memahami tampilan jumlah pengunjung antara kedua website Kementerian Agama. kedua,Easy of use berkaitan dengan usaha atau upaya yang dilakukan untuk menggunakan sebuah website atau seberapa mudah website dapat digunakan terlihat dan perbedaan ketersediaan data yang masih kosong dibeberapa kolom website, dan ketiga yaitu Customization and Personalization yang berkaitan dengan suatu website yang menyediakan konten atau isi yang dinamis terlihat dari tingkat popularitas sebuah berita diwebsite.